Genetics of nonsense suppressors in yeast - Tuite, M (1978)
﻿ This thesis is a genetic study of the cytoplasmically- inherited determinant [psi] of Saccharomyces cerevisiae . [psi] is a potentiator of ochre suppression. The molecular basis of [psi] was investigated using mutagenesis as a probe. The psi+ phenotype (efficient suppression) can be mutated to psi- phenotype (loss of suppression) by ultra-violet light (UV) and nitrosoguanidine (NTG) . The UV-induced mutation was a single-hit event and the pre-mutational lesion was partly photoreactivable . Repair or expression of UV-induced mutation to the [psi] determinant was under the same genetic control as for nuclear mutation. It was concluded that [psi] has a DNA genome. The 'extrachromosomal mutagens' thymidylate starvation, 5-fluorouracil, manganese chloride and cycloheximide failed to induce psi- mutants whilst guanidine hydrochloride, dimethyl sulphoxide and potassium chloride were shown to induce this mutation at frequencies up to 100%. Several other physical and chemical agents caused a high frequency of loss of the psi+ phenotype. A new class of recessive nuclear mutation (pnm) was shown to cause a loss of the psi+ phenotype. A simple comple- mentation test was devised to distinguish them from cytoplasmic psi- mutants. The dominant PNM- mutation was shown not to cause a physical loss of the [psi] genome. Two mutants with a modified PNM- phenotype were analysed. Attempts to demon- strate genetically the involvement of [psi] with the 80S ribosome were unsuccessful. The psi+ phenotype was conclusively demonstrated to be inherited independently' of the nucleus using a 'heterokaryon test'. Two models for the [psi] phenomena were proposed; one postulating the presence of a DMA 'plasmid' and one postulating the involvement of a stable, self-perpetuating metabolic state.